The Relationship of APOE ε4, Race, and Sex on the Age of Onset and Risk of Dementia - Powell, Danielle S.; Kuo, Pei-Lun; Qureshi, Riaz; Coburn, Sally B.; Knopman, David S.; Palta, Priya; Gottesman, Rebecca; Griswold, Michael; Albert, Marilyn; Deal, Jennifer A.; Gross, Alden L. (Frontiers in Neurology, 2021)
Objective: To investigate whether APOE ε4 genotype — an established risk factor for dementia — is associated with earlier age at diagnosis in addition to increased risk overall, and in secondary analysis by race and sex. Methods: We followed 13,782 dementia-free individuals (n=10,137 White, n=3,645 Black, baseline age 60-66 years) in the Atherosclerosis Risk in Communities Study for up to 30 years. Dementia was operationalized using standardized algorithms incorporating longitudinal cognitive change, proxy report, and hospital or death certificate dementia codes. We used a mixture of generalized gamma distributions to simultaneously estimate time-to-dementia, time-to-dementia-free-death, and the proportion of individuals with dementia, by APOE ε4 status (≥ 1 vs. no alleles). Results: Median age of dementia onset among APOE ε4 carriers was 81.7 years (Blacks) and 83.3 years (Whites) compared to 82.6 years (Blacks) and 85.7 years (Whites) in non-APOE ε4 carriers (p>0.05 Blacks; p<0.01 Whites). Age of dementia diagnosis did not differ by sex in ε4 carriers, but among non-carriers average age was earlier in males than females regardless of race. APOE ε4 carriers had on average a higher proportion of diagnoses; results did not differ by race or sex. Conclusions: APOE ε4 carrier status is associated with earlier age of dementia diagnosis with differences across race and sex. These findings clarify the causal role of APOE in dementia etiology, could help better identify at-risk subgroups, and may help facilitate better research trial recruitment and design.